Quasi-distributed fiber-optic temperature measurement device based on fiber Bragg gratings with metal coating - Ksenofontov, Michael A.; Polyakov, Alexandre V. (Journal of the Belarusian State University. Physics, 2026)
The fiber Bragg grating (FBG) as a multifunctional optical sensing element has a number of advantages, such as insensitivity to electromagnetic effects, high accuracy and small volume, which provides a wide range of applications. Based on the developed mathematical model, the sensitivity of FBG with metallic coating of nickel, aluminium and copper over a temperature range from −140 to +200 °C was studied. It was established that the temperature sensitivity of the FBG is not constant. This is due to the non-linear dependency of the effective refractive index of the fiber and the thermal expansion coefficient of the metal on temperature. The greatest shift in the central wavelength of radiation reflected from the FBG was recorded for the FBG with an aluminium coating. It was shown that in the temperature range from −140 to 0 °C, the sensitivity of metallised FBG increased from 6 to 37 pm/°C, and in the temperature range from 0 to +200 °C, it increased from 37 to 59 pm/°C. The sensitivity of FBG with metallic coating is 3.5– 4.0 times higher than sensitivity of FBG with polymer coating. It was found that to effectively increase the sensor’s sensitivity, the thickness of FBG metallic coating should not exceed 200 μm. To form a quasi-distributed fiber-optic sensor using a broadband optical amplifier with an 80 nm spectral gain bandwidth, it is possible to integrate up to six metallised FBGs on one fiber-optic, provided that the spectral interval of the shift in the central wavelength of radiation reflected from each FBG do not overlap within the temperature measurement range. The sensor’s ability to operate over a wide temperature range opens up wide possibilities for its application in various industries and the solving of practical problems, where electrical measurements are impractical or unsafe.